Subversive strategies in contemporary Chinese art - Liu, Yuedi.; Wiseman, Mary Bittner. (Philosophy of History and Culture, 2011)
What is art and what is its role in a China that is changing at a dizzying speed? These questions lie at the heart of Chinese contemporary art. Subversive Strategies paves the way for the rebirth of a Chinese aesthetics adequate to the art whose sheer energy and imaginative power is subverting the ideas through which western and Chinese critics think about art. The first collection of essays by American and Chinese philosophers and art historians, Subversive Strategies begins by showing how the art reflects current crises and is working them out through bodies gendered and political. The essays raise the question of Chinese identity in a global world and note a blurring of the boundary between art and everyday life.